Dreams of a more perfect union - Kersh, Rogan (Cornell University Press, 2001)
"In a Brilliantly conceived and elegantly written book, Rogan Kersh investigates the idea of national union in the United States. For much of the period between the colonial era and the late nineteenth century, he shows, "union" was the principal rhetorical means by which Americans expressed shared ideals and a common identity without invoking strong nationalism or centralized governance. Through his exploration of how Americans once succeeded in uniting a diverse and fragmented citizenry, Kersh revives a long-forgotten source of U.S. national identity."